One-year outcomes of Bent ab-interno needle goniectomy with phacoemulsification in primary glaucoma - Sushmita Kaushik; Ashok K Singh; Faisal Thattaruthody; Sandeep Chaudhary; Manik Sardana; Srishti Raj; Surinder S Pandav (Indian Journal of Ophthalmology)
Purpose: To study 1-year outcomes of bent ab-interno needle goniectomy (BANG) with phacoemulsification in patients across the glaucoma spectrum. Methods: This Prospective, noncomparative interventional study enrolled primary glaucoma patients (open-angle and angle-closure) with medically controlled intraocular pressure (IOP) and visually significant cataracts who underwent clear corneal phacoemulsification with intraocular lens placement combined with BANG using a 25-gauge needle bent as a reverse cystitome. Patients completing a minimum 1-year post-surgical follow-up were analyzed. The primary outcome was the change in antiglaucoma medications (AGM) required after surgery. Complete and qualified success was defined as IOP between 6 and 21 mm Hg without and with up to two topical AGMs. Results: Thirty eyes of 30 patients with a mean age of 60.5 ± 10.3 years were analyzed. The mean baseline IOP was 15.3 ± 3.6 mmHg, and the mean number of topical AGM was 2.6 ± 1.3. Ten patients were on systemic acetazolamide. The topical AGM requirement decreased to 0.60 ± 0.99 (P < 0.0001) and 0.87 ± 1.02 (P < 0.0001) at 6 months and 1 year, respectively. The mean IOP decreased to 13.57 ± 2.79 (P = 0.028) and 14.43 ± 2.92 mmHg (P = 0.11) at 6 months and 1 year, respectively. No patient required oral acetazolamide at the 6-month and 1-year follow-up after surgery. At 1-year, complete and qualified success was seen in 14 eyes each. Six eyes (20%) had an episode of a transient IOP spike, which resolved in 2 weeks, and one eye had hyphema, which resolved by the fourth day. There were no serious complications. Conclusions: Phacoemulsification with BANG is an effective and safe procedure for reducing the medication burden in patients with primary glaucoma.